1999
DOI: 10.1074/jbc.274.11.6963
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Residues in β-Lactamase Critical for Binding β-Lactamase Inhibitory Protein

Abstract: ␤-Lactamase inhibitory protein (BLIP) is a potent inhibitor of several ␤-lactamases including TEM-1 ␤-lactamase (K i ‫؍‬ 0.1 nM). The co-crystal structure of TEM-1 ␤-lactamase and BLIP has been solved, revealing the contact residues involved in the interface between the enzyme and inhibitor. To determine which residues in TEM-1 ␤-lactamase are critical for binding BLIP, the method of monovalent phage display was employed. Random mutants of TEM-1 ␤-lactamase in the 99 -114 loop-helix and 235-240 B3 ␤-strand reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Pro-107 is conserved through all class A ␤-lactamases that are inhibited by BLIP, and most of these enzymes have a valine or isoleucine at position 108. Both residues 107 and 108 in TEM-1 ␤-lactamase were previously shown to be important for BLIP binding (28). The fact that these hydrophobic interactions are important for binding between class A ␤-lactamases and BLIP is consistent with previous systematic analyses of protein-protein interfaces (14).…”
Section: Determination Of the Functional Epitope For Blip Binding Tosupporting
confidence: 76%
See 1 more Smart Citation
“…Pro-107 is conserved through all class A ␤-lactamases that are inhibited by BLIP, and most of these enzymes have a valine or isoleucine at position 108. Both residues 107 and 108 in TEM-1 ␤-lactamase were previously shown to be important for BLIP binding (28). The fact that these hydrophobic interactions are important for binding between class A ␤-lactamases and BLIP is consistent with previous systematic analyses of protein-protein interfaces (14).…”
Section: Determination Of the Functional Epitope For Blip Binding Tosupporting
confidence: 76%
“…The interaction area between BLIP and ␤-lactamase (2636 Å 2 ) is one of the largest among known protein-protein interactions (23). Several previous studies have focused on the TEM-1⅐BLIP complex (1,(23)(24)(25)(26)(27)(28)(29). We previously employed alanine-scanning mutagenesis to determine the functional epitopes of BLIP for binding the TEM-1 and SME-1 ␤-lactamases (1).…”
mentioning
confidence: 99%
“…Previous studies have shown that the binding between the TEM-1 ␤-lactamase and BLIP is not optimal and can be improved (38,40). Phage display has been shown to be an effective means of optimizing protein-protein interactions and therefore could be used to improve the binding between the BP46-51 peptide and various ␤-lactamases.…”
Section: Discussionmentioning
confidence: 99%
“…S. clavuligerus also produces ␤-lactam antibiotics such as cephamycins as well as a ␤-lactamase inhibitor, clavulanic acid (23). BLIP has been shown to bind to and inhibit the TEM-1 ␤-lactamase with a K i of 0.1 to 0.6 nM (38,40,45). In addition, BLIP binds to and inhibits the class A ␤-lactamases from Staphylococcus aureus, Bacillus cereus, and Bacillus licheniformis with K i values of 1 to 3 M. BLIP does not efficiently bind to class B, C, or D ␤-lactamases (45).…”
mentioning
confidence: 99%
“…Crystallographic analyses of BLIP and TEM alone and in complex gave insights into the nature of the inhibitory interaction and defined a peptide loop exposed on the surface of BLIP which interacts with the active site of the ␤-lactamase (20). While the proteinaceous nature of BLIP limits its value as a therapeutic agent, the fact that BLIP is structurally unrelated to existing small-molecule ␤-lactamase inhibitors, such as clavulanic acid and tazobactam, suggests that new classes of ␤-lactamase inhibitors based on smallmolecule derivatives of BLIP might hold clinical potential (15)(16)(17). However, this theory is predicated upon the assumption that clavulanic acid-resistant forms of ␤-lactamases will not show a parallel resistance to inhibition by BLIP.…”
mentioning
confidence: 99%